An Update into the Application of Nanotechnology in Bone Healing - Brannigan, K. (Open Orthop J, 2016)
BACKGROUND: Bone differs from other organs in that it can regenerate and remodel without scar formation. There are instances of trauma, congenital bone disorder, bone disease and bone cancer where this is not possible. Without bone grafts and implants, deformity and disability would result. Human bone grafts are limited in their management of large or non-union fractures. In response, synthetic bone grafts and implants are available to the Orthopaedic Surgeon. Unfortunately these also have their limitations and associated complications. Nanotechnology involves the research, design and manufacture of materials with a grain size less than 100nm. Nano-phase materials follow the laws of quantum physics, not classical mechanics, resulting in novel behavioural differences compared to conventional counterparts. METHODS: Past, present and future nanotechnology in bone healing literature is reviewed and discussed. The article highlights concepts which are likely to be instrumental to the future of nanotechnology in bone healing. RESULTS: Nanotechnology in bone healing is an emerging field within Orthopaedic Surgery. There is a requirement for bone healing technologies which are biochemically and structurally similar to bone. Nanotechnology is a potential solution as the arrangement of bone includes nanoscopic collagen fibres and hydroxyapatite. This review centers on the novel field of nanotechnology in bone healing with discussion focusing on advances in bone grafts, implants, diagnostics and drug delivery. CONCLUSION: The concept of nanotechnology was first introduced in 1959. Current nanoproducts for bone healing include nano-HA-paste-ostim and nano-beta-tricalcium phosphate-Vitoss. Nanophase technologies are considered to be superior bone healing solutions. Limited safety data and issues regarding cost and mass scale production require further research into this exciting field.